The Urgency of Regulating Digital Notary Protocol Supervision System by the Regional Supervisory Council in the Cybernotary Era - permatasari, aulia citra; Sukarmi, Sukarmi; Wisnuwardhani, Diah Aju (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Abstrak Notaris memiliki kewajiban menyelenggarakan protokol yang diawasi oleh Majelis Pengawas Daerah (MPD). Di era digital dan cybernotary, mekanisme pengawasan manual dinilai tidak lagi memadai dalam menjawab tuntutan efisiensi, transparansi, dan akuntabilitas. Meski telah ada inisiatif sistem berbasis teknologi seperti SIEMON, belum tersedia regulasi yang secara khusus mengatur mekanisme pengawasan protokol notaris melalui sistem digital. Kekosongan hukum ini berpotensi menimbulkan ketidakpastian hukum dan melemahkan fungsi pengawasan. Penelitian ini bertujuan menganalisis urgensi pengaturan pengawasan digital oleh MPD dalam menghadapi perkembangan cybernotary. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Analisis dilakukan melalui teori konvergensi hukum dan teknologi, teori hukum progresif, teori kepastian hukum, serta teori kewenangan untuk memahami kelemahan regulasi yang ada dan merumuskan arah pengaturan ideal. Hasil penelitian menunjukkan bahwa sistem pengawasan manual tidak lagi relevan dengan perkembangan masyarakat digital dan kebutuhan layanan hukum modern. Regulasi baru diperlukan untuk memastikan kepastian hukum, integritas jabatan notaris, serta perlindungan hukum bagi masyarakat. Dari aspek filosofis, yuridis, dan sosiologis, pengaturan ini mendesak untuk diwujudkan sebagai dasar hukum yang adaptif terhadap transformasi teknologi, sekaligus menjamin profesionalisme notaris sebagai officium nobile. Kata Kunci: Cybernotary, Pengawasan Digital, Protokol Notaris, Majelis Pengawas Daerah, Kepastian Hukum. Abstract Notaries are obliged to manage protocols under the supervision of the Regional Supervisory Council (MPD). In the digital and cybernotary era, conventional manual supervision mechanisms are no longer adequate to address the demands for efficiency, transparency, and accountability. Although initiatives such as SIEMON have been introduced, there is still no specific regulation governing technology-based supervision of notarial protocols. This legal vacuum may result in uncertainty and weaken supervisory functions. This study aims to analyze the urgency of regulating digital supervision by MPD in response to the development of cybernotary practices. The research employs normative legal methods using statutory and conceptual approaches. The analysis applies the theory of law and technology convergence, progressive law theory, legal certainty theory, and authority theory to examine current regulatory shortcomings and formulate the direction of ideal regulation. The findings reveal that manual supervision is no longer relevant to the dynamics of a digital society and the needs of modern legal services. New regulations are required to ensure legal certainty, uphold the integrity of the notary office, and protect public interests. Philosophical, juridical, and sociological considerations highlight the urgency of establishing adaptive regulations that align with technological transformation while ensuring the professionalism of notaries as officium nobile. Keywords: Cybernotary, Digital Supervision, Notary Protocol, Regional Supervisory Council, Legal Certainty